1991
DOI: 10.2514/3.10627
|View full text |Cite
|
Sign up to set email alerts
|

Steady and unsteady solutions of the incompressible Navier-Stokes equations

Abstract: An algorithm for the solution of the incompressible Navier-Stokes equations in three-dimensional generalized curvilinear coordinates is presented. The algorithm can be used to compute both steady-state and time-dependent flow problems. The algorithm is based on the method of artificial compressibility and uses a third-order flux-difference splitting technique for the convective terms and the second-order central difference for the viscous terms. Time accuracy is obtained in the numerical solutions by subiterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 407 publications
(176 citation statements)
references
References 26 publications
6
169
0
Order By: Relevance
“…They often rely on the use of suitable relaxation parameters [28] in order to reach convergence for the stiff coupled problem. In [68], a comparison between ACM and pressure-correction techniques is given and in [2], a comparison of two pressure-correction algorithms showed the overall better performances of PISO-like algorithms over SIMPLE ones.…”
Section: Semi-implicit Non-linear Solver For the Fluid Problemmentioning
confidence: 99%
“…They often rely on the use of suitable relaxation parameters [28] in order to reach convergence for the stiff coupled problem. In [68], a comparison between ACM and pressure-correction techniques is given and in [2], a comparison of two pressure-correction algorithms showed the overall better performances of PISO-like algorithms over SIMPLE ones.…”
Section: Semi-implicit Non-linear Solver For the Fluid Problemmentioning
confidence: 99%
“…To obtain timedependent solutions using this method, an iterative procedure can be applied in each physical time step such that the continuity equation is satisfied. Merkle and Athavale [30] and Rogers et al [31] reported successful computations using this pseudo-time iteration approach.…”
Section: Artificial Compressibility Methodsmentioning
confidence: 99%
“…A variety of iterative schemes can be implemented in conjunction with the upwind schemes. For example, Rogers et al [31] solved the resulting set of numerical equations using an unfactored line relaxation scheme similar to that employed by MacCormack [a].…”
Section: Numerical Schemesmentioning
confidence: 99%
“…We use the artificial compressibility method which was first developed by Chorin (1967) and since then has been developed by various researchers for the solution of steady and unsteady flow fields (e.g. Rogers et al, 1990;Rogers et al, 1991;Pappou and Tsangaris, 1997). Our time accurate solver utilizes hybrid meshes of triangles and quadrilaterals in 2D and tetrahedra, pyramids, prisms and hexahedra in 3D.…”
Section: Introductionmentioning
confidence: 99%